Optimization tool for small hydropower plant resource planning and development: A case study - Antans Sauhats; Hasan Huseyin Coban (Journal of Advanced Research in Natural and Applied Sciences)
The dimensions and significance of the modern power systems prove the necessity to change the principles of energy generation and power supply planning and management. In order to decrease carbon dioxide emissions, fight climate change, not being attached to fuel resources, and increase energy security while decreasing dependence on foreign countries, governments of many countries are increasing the share of renewable energy in electricity production and have taken actions to exploit their domestic resources, which is why renewable energy is an essential and important issue in today‘s world and also in the future it may continue to play a globally essential role. The study addresses model applications, optimization techniques, and operational issues. The main goal was devoted to the problem of small-scale hydropower plant control regime optimization. The task of determining small hydropower plant operation conditions is solved by striving for maximum profit by looking at the cases of known variations of prices in the market environment. An optimization tool known as the Quasi-Newton method for nonlinear optimization tasks is used to plan energy generation under uncertainties. The opportunity to apply the Monte-Carlo method for the feasibility study is demonstrated